Energy and exergy analysis of a renewable energy-driven ion recovery system for hydroponic greenhouses - Ragad F. Alshebli (16855098) (2022)
Providing agricultural needs is a common issue, especially in areas suffering from hot weather, freshwater scarcity, and unsuitable soil for farming. This paper aims to design and analyze a renewable energy-driven ion recovery system for hydroponic greenhouses using energy and exergy analyses. The objectives of the designed multigeneration system are recovering beneficial ions from crystallizing desalination waste brine, providing the needed fertilizers for hydroponic farming, integrating wind energy and a high-temperature fuel cell into the system to generate electricity uninterruptedly, integrating solar thermal energy into the system to generate the required heat for the absorption cooling unit. This study performs thermodynamic analysis on the system by writing energy, entropy, and exergy balance equations and evaluates the efficiencies of the subsystems and the overall system. Several sensitivity analyses are conducted to obtain the effects of different parameters on the system, such as the mass flow rate, salinity, and recovery ratio. This study proposes a unique integrated system that provides a new sustainable way to recover the needed ions for hydroponic farming from saline groundwater, in addition to groundwater desalination, using freezing desalination and electrodialysis systems assisted with renewable energy resources, in a more sustainable, efficient, and feasible manner. The system's total required electrical and thermal energy values are 518 kW and 150 kW, respectively, with overall energy and exergy efficiencies of 16.1 % and 13.4 %, respectively. The output mass flow rate amount of the recovered ions are Sodium (Na) 4.5 g/s, Sulphate (SO4) 0.624 g/s, Magnesium (Mg) 0.298 g/s, Calcium (Ca) 0.0936 g/s, and Potassium (K) 0.089 g/s. Other Information Published in: Sustainable Energy Technologies and Assessments License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.seta.2022.102628